Penerapan Jalan Kaki Terhadap Kadar Gula Darah Pada Lansia Dengan Diabetes Mellitus Di Desa Mliwis - Anisa Yulia Putri Pramesti; Tri Susilowati (Lembaga Pengembangan Kinerja Dosen, 2023)
Background : The elderly will experience various declines that have an impact on one of the problems in the endocrine system, namely diabetes mellitus. One of the reasons for lack of physical exercise. Data from Riskesdas 2018, the prevalence of diabetes mellitus diagnosed aged 65 to 74 years is 6.03%. Based on data from PKD Mliwis cadres, there were 76 cases of elderly people with DM. One of the recommended physical exercises for diabetic patients is walking. Walking can help muscles absorb blood sugar in the body. Purpose: To find out the results of implementing walking in the elderly on blood sugar levels in Mliwis Village. Method: This type of case study research uses descriptive research methods. Prior to the research, interviews and observations were carried out through observation sheets (pre-test) and after the intervention, results were observed (post-test). Management of diabetes mellitus by walking is given 3 times in 1 week. This therapy is given for 3 days in 30 minutes at one meeting. Results: Obtained an average reduction in sugar levels in the first respondent by 11,6 mg/dl while the second respondent obtained an average decrease of 16 mg/dl. Conclusion: This walking therapy can reduce blood sugar levels in 2 respondents.